(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
The global health scenario is facing new challenges due to global warming and economic down-turn that are now threatening health development. It is therefore crucial that all systems of medicine whether conventional or traditional are beneficial and not deleterious to the health and well-being of the people must play their respective roles in promoting health, in preventing disease, in curing the sick, and in rehabilitating the infirm. It is through these concerted efforts that tangible gains can be achieved. Herbal medicines constitute the main component of traditional medicine, which have been used since thousands of years. They have made significant contribution to human health through their health pro-motive, curative and rehabilitative properties and in the prevention of illnesses. Indeed, many herbal remedies used traditionally have become modern medicines through drug development. Long tradition use of many herbal remedies and experiences passed on from generation to generation has brought about reliance by the people on herbal medicines. It is envisaged that this publication will be instrumental in revitalizing primary health care in empowering community participation in self-care, in promoting the application of appropriate technology that is socially and culturally acceptable to the people, in making the health system more people-centered, and in improving equitable access to national health systems.